Etika Lingkungan Filsafat Ekologi: Pemikiran Kontemporer Tentang Tanggung Jawab Manusia Terhadap Alam - Nome, Hot; H. A Tuan, Yoram; Lawalata, Mozes (Sekolah Tinggi Teologi Injili Indonesia Palu, 2023)
This article elucidates the concept of environmental ethics in the context of ecological philosophy, focusing on human responsibility towards nature. Through analysis of contemporary thought, the article reveals key aspects underpinning the relationship between humans and the environment. Within this framework, human responsibility towards nature is understood as a profound moral obligation that requires awareness of its impacts on the global ecosystem. By integrating ideas from various philosophical traditions, this article presents a conceptual framework that can help guide individual and societal actions towards greater ecological awareness and responsibility.